Autosomal indels distribution in Metropolitan Manila, Philippines. (December 2015) - Magalhães, M.C.A.; Amorim, A.; Gusmão, L.; Gorostiza, A.; González-Martín, A.; Pereira, R.
Abstract: The Philippines are a group of islands in the Asia-Pacific region harboring a high diversity of cultures, languages and people due to various migration waves and different degrees of admixture between neighboring groups. In this work we studied the most populous region of the country – Metropolitan Manila – with a set of small autosomal insertion deletion (indel) polymorphisms, to assess their genetic diversity and usefulness in forensic context. Using a single-tube multiplex reaction we characterized 38 indels in 195 individuals born in the National Capital Region, allowing to establish an allele frequency database for future reference in forensic applications. The genetic diversity observed was high (average heterozygosity = 0.40890), similar to previous studies in other East Asian populations, and the marker set reached good levels of informativeness, with a combined power of discrimination of 99.999999999997% and combined power of exclusion of 99.50%. In conclusion, our study showed that this simple indel multiplex can be useful for forensic applications in Metropolitan Manila Filipino population.